Environmental Risk Factors and Acute Lymphoblastic Leukaemia in Childhood (2017)
Objectives: To verify the paper of environmental risks in the process of developing Acute lymphoblastic leukemia (ALL) in childhood. Materials and methods: A search was conducted on scientific literature in order to evaluate the role of environmental risk factors in acute lymphoblastic leukemia development. Results: The environmental role in development of all in children is unknown. The two steps theory proposed by Greaves in 1988 is the most acceptable hypothesis. One first event occurs in uterus or near the moment of birth; this mutation induces the development of pre-leukemia clones. Another event, happening in the early infancy, would develop this rst pre-leukemia clone into clinical leukemia. Based on the environmental events linked to other types of leukemia and in other studies, some risk factors have been proposed as inducing the mutations leading to all. Radiation (ionizing or not), infectious agents, and chemical products are thought to be the responsible for the disease. In the last decades, many authors tried to found an association between these risk factors and the development of childhood ALL. The results however were inconclusive and even contradictories. Ionizing radiation is the only one proved to play a role in the development of leukemia. Conclusion: As leukemia is a disease that affects children, costs of this pathology are high when talking about money expend for diagnosis and treatment and when thinking on the social and psychological burden. Considering the theory proposed by Greaves, there are at least, two moments, when the patient should avoid the exposition that leads to leukemia. Therefore, it is very important to nd the real risk factor or factors that are involved in the process.